Bio-based master batch for hot melt adhesive and preparation method of bio-based master batch
By treating coffee grounds in a ball mill and adding inorganic ore particles and surface modifiers, the modified coffee grounds and inorganic ore mixed particles are formed, and combined with plastic particles, etc. are treated in a twin-screw extruder, the existing hot melt is solved. The shortcomings of glue products in antibacterial, deodorization, viscosity, low temperature performance and shape retention rate have achieved the performance improvement and sustainable development of bio-based masterbatches for hot melt adhesives.
Patent Information
- Application Number
- CN202411707868.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
The existing hot melt adhesive products have shortcomings in antibacterial, deodorization, viscosity, low temperature performance and shape retention, which limits their application range and performance.
By treating coffee grounds in a ball mill, adding inorganic ore particles and surface modifiers, the modified coffee grounds and inorganic ore mixed particles are formed, and combined with plastic particles, compatible agents and additives in a twin-screw extruder, prepare Bio-based masterbatch for hot melt adhesive.
The bio-based masterbatch for hot melt adhesives has been achieved to improve antibacterial deodorization, good viscosity, low temperature resistance and shape retention. At the same time, the preparation process is simplified, production costs are reduced, and sustainable development and resource recycling are promoted.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hot melt adhesives, and in particular to a bio-based masterbatch for hot melt adhesives and a preparation method thereof. Background Art
[0002] Insoles are widely used in the fields of shoemaking, health care, special functions, etc. The insoles used in the shoemaking industry are mainly used to match the outsole and midsole of shoes to make corresponding shapes; size plates are made according to the last plate or panel, and the corresponding shapes are made. Existing insoles are generally composed of elastomer pads and fabric surface layers. During production, elastic base pads made of EVA (ethylene-vinyl acetate copolymer), PU (polyurethane) foam or silicone are usually made first, and then adhesive is brushed on the surface of the elastic base pad, and the fabric surface layer is attached, and finally the finished product is cut and trimmed. However, this type of insole generally has the defects of poor resilience and poor breathability. It is easy to produce odor after a period of use, which affects the user experience.
[0003] The Chinese patent application number CN105400479B recently applied by the applicant discloses a method for preparing a healthy low-temperature hot melt adhesive, wherein the raw materials include the following components by weight: 45-60 parts of TPU hot melt adhesive resin, 10-20 parts of PETG, 25-30 parts of negative ion / bamboo activated carbon composite material, and 3-5 parts of compatibilizer; (1) the above raw materials are respectively put into a storage mechanism for metal removal through high-intensity magnetism; (2) the raw materials are transported to a material cylinder and stirred for 30-45 minutes until they are uniform; (3) the stirred raw materials are further subjected to secondary strong magnetic metal removal and then transported to the feed hopper of a cast extruder, and fed to a screw machine at a uniform speed according to a preset quantity through a metering feeding mechanism, and uniformly cast into a sheet through a high-temperature melt mixing and kneading of a screw machine at 130-150°C, and then cold pressed to shape.
[0004] In the above-mentioned preparation methods, there are some obvious shortcomings, which limit the performance and application range of hot melt adhesives. First, these hot melt adhesive products are insufficient in antibacterial and deodorizing capabilities, which means that they cannot effectively inhibit the growth of bacteria and eliminate bad odors, which is particularly problematic in environments with high hygiene requirements. Secondly, their viscosity performance is not ideal, which may lead to insufficient bonding strength and cannot meet the needs of some specific applications. Furthermore, these hot melt adhesives tend to become brittle in low temperature environments and lack sufficient flexibility and recovery ability when tortuously deformed, which will seriously affect their performance in cold climates or occasions where frequent bending is required. Finally, their shape retention rate is poor, which means that after long-term use or external force, the hot melt adhesive may deform, thereby affecting its appearance and function. These defects show that there is still a lot of room for improvement in product performance of bio-based masterbatches for hot melt adhesives under the existing technical solutions. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a bio-based masterbatch for hot melt adhesive, which has the advantages of simple steps and can prepare a bio-based masterbatch for hot melt adhesive that is antibacterial and deodorizing, has good viscosity, is resistant to low-temperature bending, and has good shape retention.
[0006] The second object of the present invention is to provide a bio-based masterbatch for hot melt adhesive, which has the advantages of antibacterial and deodorizing, good viscosity, resistance to low temperature bending, and good shape retention.
[0007] To achieve the above first object, the present invention provides the following technical solutions: A method for preparing a bio-based masterbatch for hot melt adhesive comprises the following steps: S1: adding coffee grounds, inorganic ore particles accounting for 1.00-5.00% of the total weight of the coffee grounds, and a surface modifier accounting for 1.00-6.00% of the total weight of the coffee grounds and the inorganic ore in a ball mill for ball milling reaction, and after the reaction is completed, post-processing is performed to obtain modified coffee grounds and inorganic ore mixed particles; S2 adds 100 parts of plastic particles, 3.00-5.00 parts of compatibilizer, 2.00-4.00 parts of auxiliary agent, and 20.00-50.00 parts of modified coffee grounds and inorganic mineral mixed particles obtained in S1 into a twin-screw extruder, and obtains a bio-based masterbatch for hot melt adhesive after melt extrusion granulation.
[0008] By adopting the above technical scheme, under the premise of resource utilization of coffee grounds, the fluidity and processing performance of the entire molten system are significantly improved by introducing inorganic mineral particles to fill and modify the coffee grounds matrix. At the same time, compatibilizers and additives are used to effectively promote the compatibility and dispersibility between the components to ensure that the coffee grounds and inorganic mineral particles can be evenly dispersed in the plastic matrix, so that the masterbatch finally prepared has also been significantly improved in terms of low-temperature bending resistance and shape retention rate; by adopting the above method, not only the preparation process of bio-based masterbatch for hot melt adhesive is simplified, and the production cost is reduced. It also realizes the reuse of coffee grounds, a renewable resource, reduces the generation of waste, and can prepare bio-based masterbatch for hot melt adhesive with antibacterial and deodorization, good viscosity, low-temperature bending resistance, and good shape retention rate.
[0009] Furthermore, in S1, the coffee grounds are pre-milled, and the particle size of the coffee grounds is controlled to be in the range of 1 to 50 μm. Through ball milling, the physical structure of the coffee grounds is refined, thereby increasing its surface area, which helps to improve the efficiency of subsequent chemical reactions; and controlling the particle size in the range of 1 to 50 μm can ensure that the coffee grounds have good reactivity during the reaction process, while avoiding the agglomeration problem that may be caused by overly fine powder; in addition, the uniformity of the particle size is crucial to the repeatability and reliability of the preparation results. In S1, this pretreatment step is a key link in achieving efficient utilization of coffee grounds.
[0010] Furthermore, in S1, the inorganic ore particles are one or a combination of calcium carbonate particles and silicon dioxide particles, and the particle size of the inorganic ore particles is controlled to be in the range of 2 to 100 μm. By controlling the particle size, it is possible to ensure that the inorganic ore particles have good dispersibility and compatibility in the composite material, thereby improving the mechanical properties and processing properties of the composite material.
[0011] Further, in the S1, the surface modifier is one or a combination of isopropyl distearate acyloxyaluminate, isopropyl dioleate acyloxy (dioctyl phosphate acyloxy) titanate, isopropyl tris (dioctyl phosphate acyloxy) titanate, isopropyl trisostearate titanate, bis (dioctyl pyrophosphate) ethylene titanate, γ-glycidylpropyl-trimethoxysilane, γ-methacryloxypropyl-trimethoxysilane, γ-aminopropyl-trimethoxysilane, γ-mercaptopropyl-trimethoxysilane, and vinyl triethoxysilane. The use of these surface modifiers can significantly improve the dispersibility and stability of the molten system, thus playing an important role in the industrial application of hot melt adhesives; through the chemical action of the surface modifier, the hydrophilicity or hydrophobicity of the masterbatch surface can be adjusted to meet the needs of different media; in addition, the introduction of surface modifiers can also improve the compatibility of the masterbatch with the substrate and enhance the mechanical properties and weather resistance of the composite material; in practical applications, selecting a suitable combination of surface modifiers according to different needs can achieve the purpose of optimizing product performance.
[0012] Furthermore, in S1, the ball milling reaction is carried out at room temperature, and during the ball milling process, all valves are closed, and no gas exchange is carried out with the external atmosphere, and the ball milling speed is controlled to be 100-500 rpm, the ball milling time is 1-4 hours, and the mass ratio of the reactant to the grinding ball is 30-100:1. After the ball milling reaction is completed, the reaction mixture is filtered to separate the unreacted solids and the grinding balls, and then the filtered product is washed to remove the residual reaction by-products, and finally the final mixed particles are obtained through a drying step, and the obtained mixed particles have a uniform particle size distribution and a high purity, which are suitable for the subsequent material preparation process.
[0013] Further, in S2, the plastic particles are one or a combination of polyethylene, polypropylene, low melting point polyethylene terephthalate, modified polyethylene terephthalate, thermoplastic polyurethane, ethylene-vinyl acetate copolymer, and polyolefin elastomer. The combination of these plastic particles has excellent processing performance and physical and chemical properties, so that the melt system can maintain good fluidity and stability during the extrusion granulation process.
[0014] Further, in S2, the compatibilizer includes one or more of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted thermoplastic polyurethane, and maleic anhydride grafted ethylene-vinyl acetate copolymer. The addition of these compatibilizers can significantly improve the compatibility between different materials, thereby improving the mechanical properties and processing properties of the composite material; for example, maleic anhydride grafted polyethylene can improve the compatibility of polyethylene with other polar polymers, and maleic anhydride grafted polypropylene is conducive to the mixing of polypropylene and polar materials; through the reasonable selection and proportion of these compatibilizers, composite materials with specific performance requirements can be prepared to meet the needs of different industrial applications.
[0015] Furthermore, in S2, the additive is one or a combination of liquid paraffin, white oil, vegetable oil, mineral oil, polyethylene wax, and polypropylene wax. The addition of the additive significantly improves the lubrication performance of the melt system, reduces friction during processing, and thus reduces energy consumption; at the same time, due to the chemical inertness of these additives, they will not react with other components, ensuring the chemical stability of the material; in addition, the use of these additives also improves the processing performance of the bio-based masterbatch for hot melt adhesives, making the material smoother during processing such as extrusion and injection molding, and improving the surface finish and dimensional accuracy of the product.
[0016] Furthermore, in the S2, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder are 60~120℃, 120~180℃, 130~165℃, 150~175℃, 130~165℃, 145~165℃, 145~165℃, and 145~165℃, respectively, and the processing time of each section is 0.1~1.2min. In each processing section of the twin-screw extruder, precise control of temperature and time is crucial to the quality of the final product; for example, the low temperature setting of the feeding section helps prevent thermal degradation of the raw materials before entering the extruder, while the temperature of the melting section needs to be high enough to ensure complete melting of the raw materials; the temperature control of the melt conveying section, mixing section and homogenization section needs to ensure that the materials are evenly mixed and plasticized during the extrusion process to form a uniform melt; the temperature setting of the air exhaust section and the vacuum exhaust section needs to take into account the removal of volatile substances while avoiding overheating of the material; finally, the temperature and time control of the metering section are crucial to ensure the dimensional accuracy and stability of the extrudate; through these fine process parameter settings, the twin-screw extruder can produce high-quality bio-based masterbatch for hot melt adhesives.
[0017] To achieve the above second purpose, the present invention provides the following technical solutions: A bio-based masterbatch for hot melt adhesive is prepared by the above preparation method.
[0018] By adopting the above technical solution, the bio-based masterbatch for hot melt adhesive not only has the function of antibacterial and deodorizing, but also has good viscosity and can maintain good tortuosity and shape stability in low temperature environment. The application of this technology not only helps to promote the sustainable development of the hot melt adhesive industry, but also opens up a new way for the comprehensive utilization of coffee grounds, and makes positive contributions to environmental protection and resource recycling.
[0019] In summary, the beneficial technical effects of the present invention are: 1. The method for preparing the bio-based masterbatch for hot melt adhesive of the present invention has the advantages of simple steps, being able to prepare the bio-based masterbatch for hot melt adhesive with antibacterial and deodorizing properties, good viscosity, resistance to low temperature bending, and good shape retention rate; 2. The bio-based masterbatch for hot melt adhesive of the present invention has the advantages of antibacterial and deodorizing properties, good viscosity, resistance to low-temperature bending, and good shape retention. DETAILED DESCRIPTION
[0020] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with specific implementation methods. Example
[0021] Embodiment 1: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (isopropyl distearate acyloxyaluminate) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained by post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 4.08 parts of a compatibilizer (maleic anhydride grafted polyethylene), 2.87 parts of an auxiliary agent (liquid paraffin), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0022] Embodiment 2: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 1-10 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 2-20 μm) accounting for 1.00% of the total weight of the coffee grounds and a surface modifier (isopropyl distearate acyloxyaluminate) accounting for 1.00% of the total weight of the coffee grounds and the inorganic mineral are added; then, a ball milling reaction is carried out at room temperature, during which all valves are closed and no gas is exchanged with the external atmosphere, and the ball milling speed is controlled to be 100 rpm, the ball milling time is 1.0 h, and the mass ratio of the reactant to the grinding ball is 30:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained by post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 3.00 parts of a compatibilizer (maleic anhydride grafted polyethylene), 2.00 parts of an auxiliary agent (liquid paraffin), and 20.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenizing section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0023] Embodiment 3: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 10-15 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 20-35 μm) accounting for 2.00% of the total weight of the coffee grounds and a surface modifier (isopropyl distearate acyloxyaluminate) accounting for 2.00% of the total weight of the coffee grounds and the inorganic mineral are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 200 rpm, the ball milling time is 1.5 h, and the mass ratio of the reactant to the grinding ball is 50:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 3.50 parts of a compatibilizer (maleic anhydride grafted polyethylene), 2.50 parts of an auxiliary agent (liquid paraffin), and 30.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0024] Embodiment 4: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 15-25 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 35-40 μm) accounting for 3.00% of the total weight of the coffee grounds and a surface modifier (isopropyl distearate acyloxyaluminate) accounting for 4.00% of the total weight of the coffee grounds and the inorganic mineral are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 3.0 h, and the mass ratio of the reactant to the grinding ball is 70:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 4.00 parts of a compatibilizer (maleic anhydride grafted polyethylene), 3.00 parts of an auxiliary agent (liquid paraffin), and 35.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0025] Embodiment 5: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 35-40 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 60-80 μm) accounting for 4.00% of the total weight of the coffee grounds and a surface modifier (isopropyl distearate acyloxyaluminate) accounting for 5.00% of the total weight of the coffee grounds and the inorganic mineral are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 400 rpm, the ball milling time is 3.5 h, and the mass ratio of the reactant to the grinding ball is 80:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 4.50 parts of a compatibilizer (maleic anhydride grafted polyethylene), 3.50 parts of an auxiliary agent (liquid paraffin), and 40.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenizing section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0026] Embodiment 6: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 40-50 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 80-100 μm) accounting for 5.00% of the total weight of the coffee grounds and a surface modifier (isopropyl distearate acyloxyaluminate) accounting for 6.00% of the total weight of the coffee grounds and the inorganic mineral are added; then, a ball milling reaction is carried out at room temperature, during which all valves are closed and no gas is exchanged with the external atmosphere, and the ball milling speed is controlled to be 500 rpm, the ball milling time is 4.0 h, and the mass ratio of the reactant to the grinding ball is 100:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained by post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 5.00 parts of a compatibilizer (maleic anhydride grafted polyethylene), 4.00 parts of an auxiliary agent (liquid paraffin), and 50.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenizing section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion and granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0027] Embodiment 7: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (silicon dioxide particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (isopropyl dioleyl (dioctyl phosphate) titanate) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, a ball milling reaction is carried out at room temperature, during which all valves are closed and no gas is exchanged with the external atmosphere, and the ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polypropylene), 4.08 parts of compatibilizer (maleic anhydride grafted polypropylene), 2.87 parts of additives (white oil), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0028] Embodiment 8: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (isopropyl tri(dioctylphosphoyloxy)titanate) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, a ball milling reaction is carried out at room temperature, during which all valves are closed and no gas is exchanged with the external atmosphere, and the ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained by post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (low-melting point polyethylene terephthalate), 4.08 parts of a compatibilizer (maleic anhydride grafted thermoplastic polyurethane), 2.87 parts of an auxiliary agent (vegetable oil), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion and granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0029] Embodiment 9: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (isopropyl titanate triisostearate) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (modified polyethylene terephthalate), 4.08 parts of a compatibilizer (maleic anhydride grafted ethylene-vinyl acetate copolymer), 2.87 parts of an auxiliary agent (mineral oil), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenizing section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion and granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0030] Embodiment 10: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (bis(dioctyloxypyrophosphate)ethylene titanate) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, a ball milling reaction is carried out at room temperature, during which all valves are closed and no gas exchange is carried out with the external atmosphere, and the ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained by post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (thermoplastic polyurethane), 4.08 parts of compatibilizer (maleic anhydride grafted thermoplastic polyurethane), 2.87 parts of additive (polyethylene wax), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0031] Embodiment 11: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (γ-glycidylpropyl-trimethoxysilane) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (ethylene-vinyl acetate copolymer), 4.08 parts of compatibilizer (maleic anhydride grafted ethylene-vinyl acetate copolymer), 2.87 parts of auxiliary agent (polypropylene wax), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0032] Embodiment 12: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (γ-methacryloxypropyl-trimethoxysilane) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyolefin elastomer), 4.08 parts of compatibilizer (maleic anhydride grafted polypropylene), 2.87 parts of auxiliary agent (liquid paraffin), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0033] Embodiment 13: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (γ-aminopropyl-trimethoxysilane) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 4.08 parts of a compatibilizer (maleic anhydride grafted polyethylene), 2.87 parts of an auxiliary agent (liquid paraffin), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0034] Embodiment 14: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (γ-mercaptopropyl-trimethoxysilane) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 4.08 parts of a compatibilizer (maleic anhydride grafted polyethylene), 2.87 parts of an auxiliary agent (liquid paraffin), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained.
[0035] Embodiment 15: A method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention comprises the following steps: S1 In a ball mill, coffee grounds are pre-milled and the particle size of the coffee grounds is controlled to be in the range of 25-35 μm; then, inorganic mineral particles (calcium carbonate particles with a particle size range of 40-60 μm) accounting for 2.70% of the total weight of the coffee grounds and a surface modifier (vinyl triethoxysilane) accounting for 3.20% of the total weight of the coffee grounds and the inorganic ore are added; then, the ball milling reaction is carried out at room temperature, and all valves are closed during the ball milling process, and no gas exchange is carried out with the external atmosphere. The ball milling speed is controlled to be 300 rpm, the ball milling time is 2.5 h, and the mass ratio of the reactant to the grinding ball is 60:1. After the reaction is completed, the modified coffee grounds and inorganic mineral mixed particles are obtained through post-treatment; S2: In a twin-screw extruder, 100 parts of plastic particles (polyethylene), 4.08 parts of a compatibilizer (maleic anhydride grafted polyethylene), 2.87 parts of an auxiliary agent (liquid paraffin), and 28.00 parts of modified coffee grounds and inorganic mineral mixed particles prepared in S1 were added. At the same time, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder were controlled to be 60-120°C, 120-180°C, 130-165°C, 150-175°C, 130-165°C, 145-165°C, 145-165°C, and 145-165°C, respectively. The processing time of each section was 0.1-1.2 min. After melt extrusion granulation, a bio-based masterbatch for hot melt adhesive was obtained. Comparative Example
[0036] Comparative Example 1 is a method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention, which is different from Example 1 in that, in S1, coffee grounds are not used.
[0037] Comparative Example 2 is a method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention, which is different from Example 1 in that, in S1, no inorganic mineral particles are used.
[0038] Comparative Example 3 is a method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention, which is different from Example 1 in that, in S1, no surface modifier is used.
[0039] Comparative Example 4 is a method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention, which is different from Example 1 in that, in S2, no compatibilizer is used.
[0040] Comparative Example 5 is a method for preparing a bio-based masterbatch for hot melt adhesive disclosed in the present invention, which is different from Example 1 in that no auxiliary agent is used in S2. Performance testing
[0041] The bio-based masterbatch for hot melt adhesive prepared in Examples 1 to 15 and Comparative Examples 1 to 5 was placed between the polyester fabric and the nylon fabric, and the two fabrics were bonded. The polyester fabric and the polyester-cotton fabric used were both purchased from the market, and the weight of the polyester fabric was 80 g / m 2 , measured at 78g / m 2 The weight of brocade fabric is 135g / m 2 , measured to be 134g / m 2 The coating thickness of the bio-based masterbatch for hot melt adhesive used is 80μm.
[0042] The peel strength was tested with reference to GB / T 2790-1995 standard; the ammonia removal rate was tested with reference to GB / T 33610.2-2017 standard; the bonded fabric was placed at -15°C, folded in half for multiple times, and the appearance changes at the folded part were observed, and the number of low-temperature bending resistance and the corresponding shape retention rate were tested. The test results are shown in Table 1.
[0043] Table 1 Test items Peel strength Ammonia removal rate Low temperature resistance bending times Shape retention Example 1 4.01N / 25mm 85% 1000 95% Example 2 3.28N / 25mm 79% 1200 93% Example 3 3.01N / 25mm 84% 900 90% Example 4 3.32N / 25mm 89% 900 89% Example 5 3.56N / 25mm 91% 900 88% Example 6 3.85N / 25mm 83% 900 85% Example 7 3.42N / 25mm 85% 1000 89% Example 8 3.93N / 25mm 79% 1100 90% Example 9 3.23N / 25mm 91% 1200 94% Example 10 3.87N / 25mm 88% 1500 95% Embodiment 11 3.24N / 25mm 85% 1300 93% Example 12 3.74N / 25mm 90% 1200 92% Embodiment 13 3.49N / 25mm 93% 1300 94% Embodiment 14 3.56N / 25mm 87% 1200 96% Embodiment 15 3.49N / 25mm 79% 1000 92% Comparative Example 1 4.01N / 25mm 9% 1000 95% Comparative Example 2 3.97N / 25mm 82% 800 82% Comparative Example 3 3.01N / 25mm 79% 300 67% Comparative Example 4 2.57N / 25mm 70% 400 68% Comparative Example 5 2.97N / 25mm 83% 600 83% As can be seen from Table 1, by changing the technical parameters in the preparation steps of the modified coffee grounds and inorganic ore mixed particles and the bio-based masterbatch for hot melt adhesive in Examples 1 to 15, the product performance of the masterbatch also changes irregularly, among which the comprehensive performance of the masterbatch prepared in Example 1 is the best; In contrast, in Comparative Examples 1 and 2, after not using coffee grounds or inorganic mineral particles, the peel strength of the masterbatch was not affected, but the deodorization performance and low-temperature bending resistance were affected. This is mainly because coffee grounds have a significant deodorization function, and by adding inorganic mineral particles during the grinding process of coffee grounds, the particle size of coffee grounds particles can be significantly reduced, the compatibility of coffee grounds with plastic particles can be improved, and the low-temperature bending and shape retention performance of the hot melt adhesive can be improved. In addition, Comparative Examples 3 to 5 show that surface modifiers and compatibilizers can significantly improve the low-temperature flexural and shape retention properties of hot melt adhesives. The mechanisms of the two are slightly different. The former improves the compatibility between inorganic mineral particles / coffee grounds particles and plastic particles, while the latter improves the compatibility between plastic particles and other materials. At the same time, additives can improve the processing performance of hot melt adhesives and the uniformity of each component, which is beneficial to improving the peel strength of hot melt adhesives, and also improves the low-temperature flexural and shape retention properties.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a bio-based masterbatch for hot melt adhesive, characterized in that: The following steps are included: S1: adding coffee grounds, inorganic ore particles accounting for 1.00-5.00% of the total weight of the coffee grounds, and a surface modifier accounting for 1.00-6.00% of the total weight of the coffee grounds and the inorganic ore in a ball mill for ball milling reaction, and after the reaction is completed, post-processing is performed to obtain modified coffee grounds and inorganic ore mixed particles; S2 adds 100 parts of plastic particles, 3.00-5.00 parts of compatibilizer, 2.00-4.00 parts of auxiliary agent, and 20.00-50.00 parts of modified coffee grounds and inorganic mineral mixed particles obtained in S1 into a twin-screw extruder, and obtains a bio-based masterbatch for hot melt adhesive after melt extrusion granulation.
2. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In S1, the coffee grounds are ball-milled in advance, and the particle size of the coffee grounds is controlled to be in the range of 1 to 50 μm.
3. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In the above S1, the inorganic mineral particles are calcium carbonate particles, silicon dioxide particles or a combination of the above, and the particle size of the inorganic mineral particles is controlled to be in the range of 2-100 μm.
4. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In the S1, the surface modifier is one or a combination of isopropyl distearate acyloxyaluminate, isopropyl dioleate acyloxy (dioctyl phosphate acyloxy) titanate, isopropyl tris (dioctyl phosphate acyloxy) titanate, isopropyl trisostearate titanate, bis (dioctyl pyrophosphate) ethylene titanate, γ-glycidylpropyl-trimethoxysilane, γ-methacryloxypropyl-trimethoxysilane, γ-aminopropyl-trimethoxysilane, γ-mercaptopropyl-trimethoxysilane, and vinyl triethoxysilane.
5. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In S1, the ball milling reaction is carried out at room temperature. During the ball milling process, all valves are closed, and no gas exchange is performed with the external atmosphere. The ball milling speed is controlled to be 100-500 rpm, the ball milling time is 1-4 h, and the mass ratio of the reactant to the grinding ball is 30-100:
1.
6. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In S2, the plastic particles are one or a combination of polyethylene, polypropylene, low melting point polyethylene terephthalate, modified polyethylene terephthalate, thermoplastic polyurethane, ethylene-vinyl acetate copolymer, and polyolefin elastomer.
7. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In S2, the compatibilizer includes one or a combination of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted thermoplastic polyurethane, and maleic anhydride grafted ethylene-vinyl acetate copolymer.
8. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In S2, the auxiliary agent is one or a combination of liquid paraffin, white oil, vegetable oil, mineral oil, polyethylene wax, and polypropylene wax.
9. The method for preparing a bio-based masterbatch for hot melt adhesive according to claim 1, characterized in that: In the S2, the processing temperatures of the feeding section, melting section, melt conveying section, mixing section, air exhaust section, homogenization section, vacuum exhaust section and metering section of the twin-screw extruder are 60~120℃, 120~180℃, 130~165℃, 150~175℃, 130~165℃, 145~165℃, 145~165℃, and 145~165℃, respectively, and the processing time of each section is 0.1~1.2min.
10. A bio-based masterbatch for hot melt adhesive, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation Method of Healthy Low-Temperature Hot Melt Adhesive
CN105400479B